The combination of resveratrol and Bletilla striata polysaccharide decreases inflammatory markers of early osteoarthritis knee and the preliminary results on LPS‐induced OA rats - Tzu‐Chieh Lin; Jhih‐Ni Lin; I‐Hsuan Yang; Christina Soong; Ya‐Jyun Liang; Subhaini Jakfar; Chun‐Che Yen; Hwa‐Chang Liu; Hsuan‐Yu Chen; Feng‐Huei Lin (Bioengineering & Translational Medicine, 2023)
Abstract Osteoarthritis (OA) of the knee is characterized by progressive deterioration and loss of articular cartilage with associatedstructural and performance changes in the entire joint, and current treatments for OA only aim to relieve symptoms, rather than to prevent or reverse disease progression. Recently, treatments targeting “early osteoarthritis” (EOA) have attracted attention. However, during EOA stage, chondrocytes may change behaviors to express pro‐inflammatory cytokines and free radicals, which would cause detrimental effects to the synovial cavity and further cartilage wear. In this study, we combined resveratrol (Res) and Bletilla striata polysaccharide (BSP) as anti‐inflammatories and antioxidants to diffuse free radicals and to alleviate inflammation from the synovial cavity both short term and long term. The current study introduced a new method for harvesting BSP from as‐received Bletilla striata to achieve high yields, shortened extraction times, and maintained structure/functions. In addition, it combined Res and home‐extracted BSP (Res‐BSP) to alleviate oxidative stress and inflammation in a Lipopolysaccharide (LPS)‐induced OA model. The gene expressions of inflammatory genes iNOs, IL‐1β, IL‐6, and MMP‐13 were upregulated 5.7‐fold, 6.5‐fold, 8.6‐fold, and 4.5‐fold, respectively on OA‐like chondrocytes and the gene expressions were significantly downregulated to 3.3‐fold, 2.1‐fold, 4.9‐fold, and 0.1‐fold, respectively, once OA‐like chondrocytes were treated with Res‐BSP (p < 0.05, compared with OA‐like chondrocytes). The gene expressions of chondrogenic genes TGFβ1, SOX9, and type II collagen were downregulated by 0.8‐fold, 2.2‐fold, and 0.8‐fold, respectively, based on the control group as a baseline. While it was significantly upregulated by 3.4‐fold, 0.32‐fold, and 0.4‐fold, respectively, once OA‐like chondrocytes were treated with Res‐BSP. (p < 0.05, compared with OA‐like chondrocytes). Finally, we elucidated the role of Res‐BSP in EOA in suppressing COX‐2 and activating p‐Smad 2/3 and p‐Erk1/2. We believe that the combination of Res and BSP has great potential as an alternative therapeutic strategy for EOA treatment in future.